The influence of some parameters on the flow properties of bulk solids - Hann, Damjan (Strojniški vestnik, 2009)
Numerous studies in the past attempted to characterize bulk solids. However, some characteristics of bulk solids still remain insufficiently understood. This paper presents some interesting results about the influence of the particle size distribution and moisture content on the unconfined yield strength of bulk solids. Since characterization of bulk solids goes beyond determining the above mentioned properties, a novel attritor which was designed and used in our laboratory as a significant part of a new method for determining the influence of particle shape on the unconfined yield strength of a bulk solid, is presented.
Keywords: sipki materiali; tok snovi; porazdelitev velikosti delcev; vlaga